Imine-stabilized silylium ions: synthesis, structure and application in catalysis. Issue 10 (13th February 2023) - Dajnak, Aymeric; Shi, Limiao; Altınbaş Özpınar, Gül; Lenk, Romaric; Saffon-Merceron, Nathalie; Baceiredo, Antoine; Kato, Tsuyoshi; Müller, Thomas; Maerten, Eddy
Abstract : Novel imine-stabilized silylium ions as efficient catalysts for the hydrosilylation and allylsilylation of carbonyl derivatives under mild conditions. Abstract : Novel norbornene-based imine-stabilized silylium ions 2 have been synthesized via the simple reaction of sulfide-stabilized silylium ion 1 with carbonyl derivatives. Those silylium ions were fully characterized in solution and in the solid state by NMR spectroscopy and X-ray diffraction analysis as well as DFT calculations. Unlike the previously reported phosphine-stabilized silylium ion VI, behaving as a Lewis pair, calculations show that 2 have a strong Lewis acid character. Indeed, imine-stabilized silylium ions 2 are able to activate Si–H bonds and catalyzed the hydrosilylation of carbonyl derivatives under mild conditions.